STORAGE OF POMEGRANATE FRUITS IN COLD CHAMBERS: PREVENTION OF MICROBIOLOGICAL SPOILAGE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study examines the storage of pomegranate fruits in cold chambers with a focus on preventing microbiological spoilage. The research analyzes the main factors affecting fruit quality during post-harvest handling, including temperature, humidity, ventilation, and sanitation conditions. Modern preservation technologies and preventive measures such as controlled-atmosphere storage, antifungal treatments, and hygienic handling practices are reviewed. The findings highlight the importance of proper cold-chain management in reducing losses, maintaining nutritional value, and ensuring the marketability of pomegranates during long-term storage.